Sanctions, Perceived Anger, and Criminal Offending - Carmichael, Stephanie (Journal of quantitative criminology, 2004)
In articulating models of offender decision-making, researchers have tended to focus on either deterrence/rational choice or situational/emotional considerations. In this paper, we merge these two lines of inquiry and examine how rational choice considerations and perceived angry reactions inter-relate in predicting assaultive violence. Using data collected on a random sample of young adults, we assess three hypotheses. First, that both rational choice and perceived anger exhibit additive effects on assault. Second, that perceived anger influences how rational choice considerations are interpreted. Third, that rational choice considerations influence assault under different levels of perceived anger, and in particular, that the effect of sanction threats fall apart under high perceived anger. Future theoretical and empirical directions are outlined.